FORMULATION OF THE 4th NATIONAL SYMPOSIUM ON AGROINDUSTRY “STRENGTHENING OF AGROINDUSTRY: THE MOVEMENT FOR NATIONAL PROSPERITY” BOGOR, SEPTEMBER 24TH, 2011 - Nastiti , Eriyatno, Abdul A. Darwis, Irawadi Jamaran,Machfud, Aji Hermawan E. Gumbira-Sa’id, M. Zein (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACTAgroindustry should be developed within the framework of the economic order based on local resources, community-oriented, and dedicated to build a better life for all, and not only increase profit and growth. Imbued with patriotic zeal, the dynamics of such systems requires courage and creative change of measuring the success of economic development. The principles of sustainability are needed by considering of the balance of 3P (people, planet, and profit) and the implications for policy attention to three aspects, namely social, ecological, and effort. Various aspects of agro-industries run nowadays need to be transformed significantly including aspects of finance, technology, management, institution, and education. Some strategic thougth in those aspects were formulated in the Forth National Symposium on Agroindustry with the theme of “Strengthening Agroindustry: the Movement for National Prosperity”, which was held in Bogor on 24 September 2011.Keywords: agroindustry, strengthening, technology, education, prosperity